Aquatic Therapy as a Non-Pharmacological Rehabilitation Approach for Post-Stroke Elderly: A Narrative Review - Zanzabil Adwa Fitrian; Luh Ade Lela Arika (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Stroke is a dangerous non-communicable disease. Stroke in older people impacts the normal quality of life. In this case, it causes the elderly to experience physical and psychological disorders that affect quality of life. This study aims to analyze and assess the effectiveness of aquatic therapy, a non-pharmacological intervention, in improving the quality of life of older adults after stroke. The research used a narrative review, drawing on relevant scientific journal articles from databases such as Google Scholar, PubMed, and Scopus. The analysis of five journals selected using PRISMA indicates that aquatic therapy has a positive impact on the quality of life of post-stroke older adults. The findings from the literature analysis in this study indicate that aquatic therapy has a positive effect on the quality of life of older adults after stroke. Aquatic therapy has a physical impact by improving balance, posture, flexibility, range of motion (ROM), muscle strength, and reducing pain. Regarding psychological impacts, aquatic therapy improves mood and decreases depression and anxiety in post-stroke older adults.